Caspase1/11 signaling affects muscle regeneration and recovery following ischemia, and can be modulated by chloroquine - Ulka Sachdev; Ricardo Ferrari; Xiangdong Cui; Abish Pius; Amrita Sahu; Michael Reynolds; Hong Liao; Ping Sun; Sunita Shinde; Fabrisia Ambrosio; Sruti Shiva; Patricia Loughran; et al. (BMC, 2020)
Abstract Background We previously showed that the autophagy inhibitor chloroquine (CQ) increases inflammatory cleaved caspase-1 activity in myocytes, and that caspase-1/11 is protective in sterile liver injury. However, the role of caspase-1/11 in the recovery of muscle from ischemia caused by peripheral arterial disease is unknown. We hypothesized that caspase-1/11 mediates recovery in muscle via effects on autophagy and this is modulated by CQ. Methods C57Bl/6 J (WT) and caspase-1/11 double-knockout (KO) mice underwent femoral artery ligation (a model of hind-limb ischemia) with or without CQ (50 mg/kg IP every 2nd day). CQ effects on autophagosome formation, microtubule associated protein 1A/1B-light chain 3 (LC3), and caspase-1 expression was measured using electron microscopy and immunofluorescence. Laser Doppler perfusion imaging documented perfusion every 7 days. After 21 days, in situ physiologic testing in tibialis anterior muscle assessed peak force contraction, and myocyte size and fibrosis was also measured. Muscle satellite cell (MuSC) oxygen consumption rate (OCR) and extracellular acidification rate was measured. Caspase-1 and glycolytic enzyme expression was detected by Western blot. Results CQ increased autophagosomes, LC3 consolidation, total caspase-1 expression and cleaved caspase-1 in muscle. Perfusion, fibrosis, myofiber regeneration, muscle contraction, MuSC fusion, OCR, ECAR and glycolytic enzyme expression was variably affected by CQ depending on presence of caspase-1/11. CQ decreased perfusion recovery, fibrosis and myofiber size in WT but not caspase-1/11KO mice. CQ diminished peak force in whole muscle, and myocyte fusion in MuSC and these effects were exacerbated in caspase-1/11KO mice. CQ reductions in maximal respiration and ATP production were reduced in caspase-1/11KO mice. Caspase-1/11KO MuSC had significant increases in protein kinase isoforms and aldolase with decreased ECAR. Conclusion Caspase-1/11 signaling affects the response to ischemia in muscle and effects are variably modulated by CQ. This may be critically important for disease treated with CQ and its derivatives, including novel viral diseases (e.g. COVID-19) that are expected to affect patients with comorbidities like cardiovascular disease.